Free amino acid profiles during ripening of Port Salut Argentino cheese after frozen storage - Verdini, Roxana Andrea (2002)
Free amino acid profiles of Port Salut Argentino cheeses at different storage conditions (ripening with and without previous frozen storage), ripening times (1, 6, 13, 27, and 56 d), and cheese zones (central and external) were studied. Derivatization with o-phtaldialdehyde and a C18 column were used for chromatographic separations. Principal component analysis reduced data to 2 dimensions where unripened cheeses (1 to 13 d) were grouped independently of ripening time, sampling zone, and storage condition. Ripened cheeses (27 and 56 d) showed scattering according to ripening time. The contribution of free amino acid profiles to quality in cheeses preserved by frozen storage may be considered similar to that in traditionally ripened cheeses.